Developing Technical Skills in Second-Grade Students of Hiroshima College: A Practical Training Program and Evaluation - MURANAKA, Shota; MARUYAMA, Masahiro; HAMASAKI, Atsushi (The Bulletin of National Institute of Technology, Hiroshima College, 2024)
This paper presents the practical training materials for second-grade students at our college and reports the findings of an investigation into the students' evaluation of the materials. The materials cover operating CAD software to draw patterns on a circuit board, assembling the circuit board with electrical components, and　measuring the voltage of the circuit board. Students responded to several surveys about the material following their practical training. The results of the student surveys on the material indicate that students' technical skills improved, and their interest in the practical training increased.